Digital Exercisers in Students Training for the Unified State Exam in Mathematics - Chernetskaya, Tatyana (Computer Tools in Education, 2021)
The article considers two types of digital exercisers for preparing students for the Unified State Exam in mathematics at the advanced level: exercises for training in solving problems with  a short answer (the first part of the Unified State Exam) and training simulators for preparing for solving problems with a detailed answer (the second part of the Unified State Exam). The first type of the digital exercises is characterized by the ability to repeatedly solve both problems of a certain type, and the variants formed from them, similar to the variants of the Unified State Exam, receiving hints in case of difficulties, automatic verification and analysis of answers. The second type of the digital exercises is characterized by a step-by-step analysis of the solution of each problem with hints and analysis of the correctness of each step, as well as the support of such simulators (in particular, on the topics “Stereometry” and “Problems with a parameter”) with dynamic models created in the interactive mathematics environment “1C:Mathkit”. The various forms of using simulators in the educational process are also discusses in the article: support for independent activity of students in the full-time educational process, support for online training with a teacher in the context of the coronavirus pandemic, and independent online training without a teacher based on specially prepared and structured training courses. In the latter case, in addition to simulators, other digital educational resources were used, the purpose of which was to increase the degree of clarity in the presentation of educational material: videos, slides, dynamic models, training exercises for problems with a detailed answer of the Unified State Exam variants.
Keywords: digital exercisers, Unified State Exam in mathematics, e-learning